Study of hydraulic conductivity and pollutant transport parameters in a municipal solid waste disposal area - Yacoub, Jhaber Dahsan [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Municipal solid waste (MSW) disposal sites play a vital role in waste management but pose significant environmental risks due to the transport of contaminants into soil and groundwater. This work examines these risks through an integrative study comprising experimental, analytical, and numerical analyses. A detailed experimental investigation of the tropical soil profile and weathered sandstone near Brazil's Bauru MSW disposal site revealed key geotechnical and hydraulic properties influencing contaminant transport, including anisotropic permeability and expansive behaviors attributed to clay minerals. Laboratory column tests using the non-reactive tracer NaCl and heavy metals (Mn, Ni, Pb) identified hydraulic conductivity (k), dispersivity (α), hydrodynamic dispersion (Dh), retardation factor (Rd), and partition coefficient (Kd) as critical parameters. Numerical simulations using CODE_BRIGHT evaluated the fate and transport of contaminants in Bauru's MSW disposal site's North-South and East-West profiles over 1, 10, and 100 years under varying leachate heads. Results show that increased leachate head accelerates breakthrough times, with horizontal flow dominating permeable soil horizons. The East-West profile exhibited greater vulnerability to contaminant migration, though sandstone layers provided some attenuation. These findings underscore the importance of integrating field data, laboratory experiments, and modeling to enhance MSW disposal site management strategies, mitigate contamination risks, and safeguard environmental resources.

Os locais de descarte de resíduos sólidos urbanos (RSU) desempenham um papel fundamental no gerenciamento de resíduos, mas apresentam riscos ambientais significativos devido ao transporte de contaminantes para o solo e as águas subterrâneas. Este trabalho examina esses riscos por meio de um estudo integrativo que inclui análises experimentais, analíticas e numéricas. Uma investigação experimental detalhada do perfil de solo tropical e do arenito intemperizado próximo ao local de descarte de RSU de Bauru, Brasil, revelaram as principais propriedades geotécnicas e hidráulicas que influenciam o transporte de contaminantes, incluindo a anisotropia quanto a permeabilidade e comportamentos expansivos atribuídos a minerais da argila. Ensaios de coluna em laboratório usando NaCl como traçador e metais pesados (Mn, Ni, Pb) identificaram a condutividade hidráulica (k), a dispersividade (α), a dispersão hidrodinâmica (Dh), o fator de retardamento (Rd) e o coeficiente de partição (Kd) como parâmetros críticos. Simulações numéricas usando o CODE_BRIGHT avaliaram o destino e o transporte de contaminantes em perfis Norte-Sul e Leste-Oeste do aterro de RSU de Bauru ao longo de 1, 10 e 100 anos sob diferentes cargas de lixiviado. Os resultados mostram que o aumento da carga de lixiviado acelera os tempos para atingir as concentrações indesejadas, com o fluxo horizontal dominando os horizontes permeáveis do solo. O perfil Leste-Oeste apresentou maior vulnerabilidade à migração de contaminantes, embora as camadas de arenito tenham proporcionado alguma atenuação. Essas descobertas ressaltam a importância da integração de dados de campo, laboratório e modelagem para aprimorar as estratégias de gerenciamento em locais de descarte de RSU, mitigar os riscos de contaminação e proteger os recursos ambientais.
Estudo da condutividade hidráulica e de parâmetros de transporte de poluentes em uma área de disposição de resíduos sólidos urbanos
Keywords: Bauru’s MSW disposal site; Weathered sandstone; Tropical soil; Contaminant transport; Numerical simulations